Evaluating psychiatrists' attitudes and expectations about pharmacists' role in psychiatry in Jordan. Issue 2 (16th March 2021) - Abdel-Qader, Derar H; Al Jomaa, Esraa E; Silverthorne, Jennifer; Shnaigat, Walid; Hamadi, Salim; Al Meslamani, Ahmad Z
Abstract: Objectives: Evaluating Jordanian pharmacists' roles in psychiatry from psychiatrists perspective. Methods: An electronic survey was sent to 100 psychiatrists registered in the Jordanian Psychiatrists Association. Statistical analysis included descriptive statistics and multivariate logistic regression. Key findings: A total of 80 psychiatrists completed the survey (response rate 80%). Most psychiatrists thought that pharmacists are unable to give individuals with mental illness enough time to discuss their medications (62/80, 77.6%) and to monitor psychotropic medications (PM) efficacy (50/80, 62.6%). Around half of respondents thought that, in the future, pharmacists would not be able to suggest PM for patients (42/80, 52.6%), nor changes in PM dosages (37/80, 46.3%). Most psychiatrists emphasized the importance of psychiatric courses to improve pharmacists' role. Conclusion: Although psychiatrists were generally not satisfied with the current role of pharmacists, they had positive expectations about pharmacists' competency to do certain activities and to assist them in designing drug therapy plans.